2022
DOI: 10.1186/s12875-022-01637-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and motives for engagement in an exercise-based cardiac rehabilitation programme in Ireland: a qualitative study

Abstract: Background Insufficient physical activity (PA) is a leading risk factor for premature death worldwide. Ireland’s public healthcare system, the Health Service Executive (HSE), has supported the development of the National Exercise Referral Framework (NERF) to tackle low levels of PA amongst those with non-communicable diseases (NCDs). ‘NERF centres’ are medically supervised PA programmes across Ireland that have established referral pathways with local hospitals and general practitioners. ULMedX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been suggested that lifestyle behavioral interventions and the encouragement for exercise beyond supervised sessions, as recommended in CR programs, may increase adherence rates [35]. Furthermore, sessions delivered by the program's psychologist addressing self-efficacy and behavioral skills could also have reinforced participant's motivation [36,37]. Reports suggest that cancer survivors and individuals with CVD may share common conditions such as those related to sleep disorders, fatigue, sexual problems, anxiety, and depression, suggesting that a comprehensive rehabilitation program could be of interest, so these motivational and educational group sessions may have also contributed to improving adherence rates in CBCR [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that lifestyle behavioral interventions and the encouragement for exercise beyond supervised sessions, as recommended in CR programs, may increase adherence rates [35]. Furthermore, sessions delivered by the program's psychologist addressing self-efficacy and behavioral skills could also have reinforced participant's motivation [36,37]. Reports suggest that cancer survivors and individuals with CVD may share common conditions such as those related to sleep disorders, fatigue, sexual problems, anxiety, and depression, suggesting that a comprehensive rehabilitation program could be of interest, so these motivational and educational group sessions may have also contributed to improving adherence rates in CBCR [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been suggested that lifestyle behavioral interventions and the encouragement for exercise beyond the supervised sessions, as recommended in CR programs, may increase adherence rates [35]. Furthermore, sessions delivered by the program's psychologist addressing self-e cacy and behavioral skills could also have reinforced participant's motivation [36,37]. Literature has shown that cancer survivors and people with CVD may share common problems, regardless the primary diagnosis, namely disturbances related to sleep disorders, fatigue, sexual problems, anxiety and depression, suggesting that a common comprehensive rehabilitation can be just as suitable, so these motivational and educational group sessions may also have contributed to improving adherence rates in CBCR [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative studies on discontinuation have examined dropout from specialised cardiac phase II rehabilitation without involving transitional phases. [21][22][23] As a result the Dropout during a 12-week exCR programme: A cohort study, called AoRTA, was established. 24 Of the 279 individuals who participated in the 12-week exCR programme mentioned above, the AoRTA study identified 103 dropouts, 72 (70%) of whom stopped at the transition point.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…How transition phases influence patient perceived pathways in split CR programmes are deficiently explored. Recent qualitative studies on discontinuation have examined dropout from specialised cardiac phase II rehabilitation without involving transitional phases 21–23…”
Section: Introductionmentioning
confidence: 99%